Performance analysis on multihop transmission using ARP routing protocol in IEEE 802.11 ad hoc network - Md Isa, Ida Syafiza; Balakrishnan, Sopna; Mohd Shaari Azyze, Nur Latif Azyze; Tuani Ibrahim, Ahamed Fayeez (Sun Publications, 2013)
Mobile Ad Hoc Network (MANET) are becoming more and more important in the modern environment. It can be used instantly to connect to the local or remote network without using the pre-existing infrastructure. The mobile or user in the network can together establish the infrastructure. In order to improve the limited range of radio transmission, multiple network ‘hops’ are needed so that the communication between the mobiles can be establish. There are varieties of protocol that had been proposed for the hopping methods but most of them suffer from high overhead. This project proposed a new method of hopping protocol for IEEE 802.11b using the existing network protocol which is Address Resolution Protocol (ARP). The ARP message is used in the network to find the MAC address of the destination. This can also be done by having multi hops where the proposed method using ARP designed will make an intermediate node act as a router in order to find the destination address and forward the data successfully. In this proposed method, the data is directly passed to the intermediate node and the intermediate node will help to find the route to the destination and passed the data to the destination node. This will reduce the transmission time. From the simulation obtained, it proved that the proposed method using the ARP protocol can works well as the existing network protocol which is Ad Hoc On-Demand Distance Vector (AODV). The simulation is composed into two types of environment which are with and without obstacles. The throughput, the packet loss and the round trip time for various distances is simulated and the results shows that the performance of the proposed method using ARP is much better compared to the AODV.